Isolasi, Identifikasi Dan Uji Antioksidan Senyawa Flavonoid Dari Ekstrak Etil Asetat Daun Tempuyung (Sonchus arvensis L.) - Ramadhani, Roshinta Anggun (Chem Info Journal, 2013)
Isolation, identification, and antioxidant activity of flavonoid compounds from ethyl acetate extract leaves tempuyung (Sonchus arvensis L.) has been done. The results of identification using UV-Vis spectrophotometer with the solvent methanol produced 2 maximum light absorption at a wavelength of 253,0 nm (bands II) and 437,5 nm (bands I). The addition of shear reagent sodium hydroxide (NaOH), sodium acetate (NaOAc), boric acid (H3BO3), aluminum chloride (AlCl3), hydrochloric acid (HCl) and analyzed using FT-IR spectrophotometer indicating group (-OH stretching) reinforced with the -OH bending, = C-H aromatic stretching, -C-H stretching asymmetry and symmetry are amplified in the presence of –C-H bend, C=O, C=C aromatic, C-O ether (bridge O), benzene substituted ortho, meta and para, allegedly the compound is 6,7,4'-trihidroksiauron. In the antioxidant assay IC50 obtained in the ethyl acetate extract and flavonoids consecutive isolates at 473,28 ppm and 421,03 ppm, with quercetin as a comparison of 64,06 ppm.